1976
DOI: 10.1901/jaba.1976.9-179
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Self‐instructional Package on Overactive Preschool Boys

Abstract: The effects of a self-instructional package on three overactive preschool boys were investigated using a multiple-baseline design across subjects. Behavioral observations of the three target subjects indicated transfer of training effects from the experimental tasks to the classroom. On-task behaviors increased dramatically concomitant with the introduction of the self-instructional package, and treatment gains were maintained 22.5 weeks after baseline was initiated. In addition, the use of an observer-expecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
70
0
2

Year Published

1984
1984
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(73 citation statements)
references
References 40 publications
1
70
0
2
Order By: Relevance
“…In applied work, self-instruction (reciting rules to oneself) and cognitive modeling have been the most common procedures used to promote self-control (Abikoff & Gittelman, 1985;Bornstein & Quevillon, 1976;Coats, 1979;Finch, Wilkinson, Nelson, & Montgomery, 1975;Friedling & O'Leary, 1979;Heider, 1971;Kendall & Braswell, 1985). Although initial success was reported, researchers (e.g., Abikoff, 1985;Abikoff & Gittelman, 1985;Barkley, 1981) increasingly have been encountering difficulties with these training packages.…”
mentioning
confidence: 99%
“…In applied work, self-instruction (reciting rules to oneself) and cognitive modeling have been the most common procedures used to promote self-control (Abikoff & Gittelman, 1985;Bornstein & Quevillon, 1976;Coats, 1979;Finch, Wilkinson, Nelson, & Montgomery, 1975;Friedling & O'Leary, 1979;Heider, 1971;Kendall & Braswell, 1985). Although initial success was reported, researchers (e.g., Abikoff, 1985;Abikoff & Gittelman, 1985;Barkley, 1981) increasingly have been encountering difficulties with these training packages.…”
mentioning
confidence: 99%
“…
We attempted to replicate an intervention program by Bornstein and Quevillon (1976), which had shown that the disruptive dassroom behavior of Head Start children could be dramatically reduced through self-instructional training. Although the subject population and procedures were quite similar across studies, our self-instructional training did not produce socially significant, durable increases in either appropriate classroom behavior or changes in teacher ratings of the children's behavior.
…”
mentioning
confidence: 99%
“…One study frequendy cited or reprinted (see Abikoff, 1979;Brundage-Aguar, Forehand, & Ciminero, 1977;Hobbs, Moguin, Tyroler, & Lahey, 1980;Kendall & Finch, 1979;Meichenbaum & Asarnow, 1979;O'Leary & O'Leary, 1977;Ross, 1981) because of its success in obtaining positive generalization to classroom behavior as a result of training on psychoeducational tasks is that by Bornstein and Quevillon (1976). These authors demonstrated that the on-task behavior of three overactive preschoolers increased from a baseline level of under 20% to above 75% as a result of self-instructional training.…”
mentioning
confidence: 99%
“…This mitigates the need for teachers to be police, and gives children a sense of responsibility for and control over their own behavior. Finally, cognitive behavior management techniques have been verified empirically as being effective in helping students change their behaviors in the classroom and in their daily life outside of school as well (Bornstein & Quevillon, 1976;Davis & Boster, 1992;Knaus & McKeever, 1977;Schleser, Meyers, Cohen, & Thackwray, 1983;Urbain & Kendall, 1980). Several different cognitive approaches now are being taught to students to help them learn about and gain control over their own activities.…”
Section: Cognitive Interventionsmentioning
confidence: 99%